Laplace Adomian Solutions to Fractional Differential Equations that Arise in Natural Science and Engineering Applications - Rabah, Fatima H. (2022)
A Master of Science thesis in Mathematics by Fatima H. Rabah entitled, “Laplace Adomian Solutions to Fractional Differential Equations that Arise in Natural Science and Engineering Applications”, submitted in June 2022. Thesis advisor is Dr. Marwan Abukhaled and thesis co-advisor is Dr. Suheil Khoury. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).